The Effects of an Empowerment Intervention on Renal Transplant Recipients: A Randomized Controlled Trial. Issue 3 (September 2016) - Hsiao, Chiu-Yueh; Lin, Li-Wei; Su, Yu-Wen; Yeh, Shu-Hui; Lee, Li-Na; Tsai, Fu-Mian
ABSTRACT: Background: Renal transplantation is a vital treatment for end-stage renal disease. To help improve quality of life after renal transplant surgery, interventions are needed to strengthen the coping skills and self-care behaviors of patients. However, most research studies on self-care after renal transplantation have addressed related factors. Few studies have examined the effects of interventions on renal transplant recipients. Purpose: This study investigated the effects of an empowerment support group on the empowerment levels and self-care behaviors of renal transplant recipients. Methods: This study was a randomized controlled trial. Eligible participants were individuals who had undergone a renal transplant within the past 20 years, were 18 years old or older, were able to read and write in Chinese, and were willing to participate. We recruited 122 renal transplant recipients from two medical centers in southern Taiwan. The renal transplant outpatients were randomly assigned into empowerment support ( n = 56) and comparison ( n = 66) groups. The developed measures as well as the content, protocols, and the two groups were assessed for reliability and validity. The intervention involved one 2-hour meeting every 2 weeks for a total of six meetings. The topics included goal setting, problem solving, coping with daily stress, seeking social support, and staying motivated. The sessions consisted of introductions that highlighted the topic, group discussions, identifying areas of difficulty with self-care behaviors after renal transplant, and developing a set of goals and strategies to overcome these problems. Results: The empowerment group reported significant increases both in terms of level of empowerment ( F = 5.29, p = .023) based on age and time interaction ( F = 9.86, p < .001) and in terms of self-care behaviors ( F = 7.15, p = .009). Moreover, these increases were significantly larger than the increases recorded by the comparison group. In addition, these increases were particularly large in the older empowerment-group participants with lower pretest scores for empowerment. Conclusions: Empowerment support may be critical to improve the empowerment and self-care behaviors of renal transplant patients. The results of this study may be applied to improve patient education and empowerment programs for renal transplant patients. Furthermore, these programs may be adjusted to take into consideration the learning preferences or needs of different age groups.